2016
DOI: 10.1111/ped.13084
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive measurement of cardiac output using AESCULON® mini after Fontan operation

Abstract: CI does not differ with laterality of the single ventricle. SRV VET, however, was significantly shorter than SLV VET in the acute postoperative period. Conversely, SRV HR was higher than SLV HR, which may mean that SRV compensates for lower VET by increasing HR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Statistically, children with less SVV variation are more likely to be in a nonresponse state. Yoshitake et al [ 26 ] used noninvasive hemodynamic monitoring to evaluate the cardiac output after Fontan operation by measuring the parameters of cardiac function in the patients with single left ventricular (SLV) and single right ventricular (SRV). Their results showed that the mean SVV (SLV : SRV) was 13.9% : 15.5%, which is similar to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Statistically, children with less SVV variation are more likely to be in a nonresponse state. Yoshitake et al [ 26 ] used noninvasive hemodynamic monitoring to evaluate the cardiac output after Fontan operation by measuring the parameters of cardiac function in the patients with single left ventricular (SLV) and single right ventricular (SRV). Their results showed that the mean SVV (SLV : SRV) was 13.9% : 15.5%, which is similar to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Statistically, children with less SVV variation are more likely to be in a non-response state. Yoshitake et al (24) used noninvasive hemodynamic monitoring to evaluate the cardiac output after Fontan operation by measuring the parameters of cardiac function in the patients with single left ventricular (SLV) and single right ventricular (SRV). Their results showed that the mean SVV (SLV : SRV) was 13.9% : 15.5%, which is similar to our study.…”
Section: Discussionmentioning
confidence: 99%
“…stated that R P remains low for many decades, but is expected to increase at older age [ 14 ]. In contrast, many failing Fontan cases pertain to the pediatric population, hence the surgery is usually performed at the age of 1–5 years [ 15 ]. Therefore, a distinction has been made between the early Fontan patient (Table 1 ) and the late Fontan patient (Table 2 ).…”
Section: Methodsmentioning
confidence: 99%